Membentuk Karakter Melalui Pendidikan Berbasis Nilai - Yusuf, Muhammad (Al-Ulum, 2013)
This article explores some evidences on unsatisfactory educational achievement. It particularly is focused on its failure in forming good character for society. This fact shows the proven that there is a â€œcrucialâ€ gap between the objectives of National education and the education result which has been gained. Al-Quran pays attention toward education which oriented to character building and understanding of plenary values. Character building according to Al-Quran should be started from â€˜the innerâ€™ of man. The values is internalized and done to be custom to form good character. Al-Quran shows some examples by asking the man to experience the objects and take lesson from them in Islam terms â€œibrahâ€ from good models which full of plenary values and is hoped to form the man who have good attitude, large knowledge, good faith and religion.